2017
DOI: 10.1016/j.antiviral.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification and evaluation of potent Middle East respiratory syndrome coronavirus (MERS-CoV) 3CL Pro inhibitors

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) causes severe acute respiratory illness with fever, cough and shortness of breath. Up to date, it has resulted in 1826 human infections, including 649 deaths. Analogous to picornavirus 3C protease (3C), 3C-like protease (3CL) is critical for initiation of the MERS-CoV replication cycle and is thus regarded as a validated drug target. As presented here, our peptidomimetic inhibitors of enterovirus 3C (6b, 6c and 6d) inhibited 3CL of MERS-CoV and severe acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 39 publications
1
93
0
Order By: Relevance
“…values were approximately 8.42 and 8.5, respectively) (Table 1). Interestingly, we observed that the EC 50 was higher than the IC 50 , which may be due to the presence of a membrane barrier or the high protease concentration (1 μM) used in the FRET assay, as previously reported (Kumar et al, 2017).…”
Section: Suppression Of Prrsv Replication By Compounds 2 3 Andsupporting
confidence: 78%
“…values were approximately 8.42 and 8.5, respectively) (Table 1). Interestingly, we observed that the EC 50 was higher than the IC 50 , which may be due to the presence of a membrane barrier or the high protease concentration (1 μM) used in the FRET assay, as previously reported (Kumar et al, 2017).…”
Section: Suppression Of Prrsv Replication By Compounds 2 3 Andsupporting
confidence: 78%
“…[40][41][42][43][44][45] However,a few low-nm-range inhibitors have been identified that can be used in combination with other protease-inhibitor therapies to help combat the virus. Many of the inhibitors are in the micromolar range in terms of binding to and inhibiting the two proteases.…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 99%
“…[46] For the purposeo ft his section, the inhibitors will be divided into categories based on the proteases that are inhibited to stop the virus from taking controlo f the host cells. [42] This potency could be adequate to combat 2019-nCoV. These compoundsa re in the low-mm range in terms of inhibition, leaving room for furtherd evelopment.…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 99%
See 1 more Smart Citation
“…Like other CoVs, PEDV depends on its own proteases, including main protease (M pro ) and papain-like protease (PL pro ) to cleave the polyprotein, and alpha CoVs have both papain-like protease 1 (PL1 pro ) and papain-like protease 2 (PL2 pro ) (Lee, 2015;Wojdyla et al, 2010). Polyprotein cleavage is required for viral maturation and thus these proteases are ideal antiviral targets (Bacha et al, 2008;Cheng et al, 2015;Chou T et al, 2008;Kumar et al, 2017;Lin et al, 2018;Park et al, 2012;Ratia et al, 2008;Wu et al, 2006). Furthermore, in contrast to highly variable spike proteins targeted by antibodies (Li et al, 2005(Li et al, , 2017; Wang et al, 2013;Wu et al, 2009), proteases with more conserved structure and catalytic function may serve as a general target across different CoVs Bailey-Elkin et al, 2014;Chou et al, 2014;Ho et al, 2015;Ratia et al, 2006;Yang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%